KNOWLEDGE AND ATTITUDE REGARDING MENTAL ILLNESS AMONG GENERAL PUBLIC - Pramod V. Kademani; Sateesh Sindhe; Shireesh Shindhe; Nagarajaiah (Indian Journal of Psychiatric Nursing)
Mental illness is a common condition, with a life time prevalence of about 40-50% in the community. However, only a few people with mental disorders generally receive treatment and about (70%) of individuals suffering from mental illness do not seek help. Additionally, the World Health Organization (WHO) estimated that 450 million people suffer from mental or behavioral disorders, of which only a small proportion receives treatment. A lack of mental health literacy can limit the optimal use of treatment services. Community knowledge of mental health problems has been found to be inadequate, whilst this lack of knowledge is a fertile soil for developing negative behavior towards mental illness. This study was conducted to assess the knowledge and attitude regarding mental illness among general public in selected rural areas of Hukkeri taluka. The cross-sectional research design was used for the present study. The data was collected for the duration of 20 days. Each day 5 subjects were interviewed. The convenient sampling technique was used to select the samples. The structured interview schedule and 3 point attitude scale was used as the main screening instrument. The results showed that the Mean percentage of knowledge score was 36.0 and the Mean percentage of attitude score was 57.95. There was a positive correlation between knowledge and attitude of subjects regarding mental illness (r=0.790). There was a significant association between source of information with level of knowledge and also there was a significant association between age and source of information with level of attitude.